The protective effect of serum carotenoids on cardiovascular disease: a cross-sectional study from the general US adult population - Wang, Min; Tang, Renzhe; Zhou, Rui; Qian, Yongxiang; Di, Dongmei (Frontiers in Nutrition, 2023)
Background: Cardiovascular disease (CVD) has become a key global health issue. Serum carotenoids are associated with CVD, while their effects on different diseases remain unclear. Herein, the relationship between the concentration of serum carotenoid and the CVD risk was investigated using nationwide adult samples obtained from the USA. Materials and methods: Data of National Health and Nutrition Examination Survey (NHANES) in 2001-2006 were employed. The association of serum carotenoids (total, lycopene, β-carotene, α-carotene, lutein/zeaxanthin, and β-cryptoxanthin) with CVD was explored by using multivariate logistic, linear and weighted quantile sum (WQS) regression analyses. 11,336 volunteers were enrolled eventually. Results: Multivariate model data showed that lutein/zeaxanthin, α-carotene, lycopene, and β-cryptoxanthin were negatively associated with the incidence of CVD (P was less than 0.05). In comparison with the first quartile, the fourth quartile was associated with α-carotene ([OR] = 0.61 [0.47-0.79]), β-cryptoxanthin (OR = 0.67 [0.50-0.89]), lutein (OR = 0.69 [0.54- 0.86]), and lycopene (OR = 0.53 [0.41-0.67]). WQS analysis revealed that serum carotenoids had negative correlation with CVD (P was less than 0.001). Additionally, dose-response analysis demonstrated a negative linear association of hypertension with all the carotenoids involved (P was larger than 0.05 for non-linearity). Conclusions: The concentration of serum carotenoids had negative correlation with the prevalence of CVD, with a more significant protective effect against heart attack and stroke.